2018
DOI: 10.3390/ani8060080
|View full text |Cite
|
Sign up to set email alerts
|

My Dog Is Not My Cat: Owner Perception of the Personalities of Dogs and Cats Living in the Same Household

Abstract: Simple SummaryA growing number of dogs and cats live together, sharing both a common home and common owner. Nevertheless, how do owners of both cats and dogs living in the same household perceive their pets’ personalities? We tried to answer this question by using a questionnaire targeted at people who owned both dogs and cats. Sociability, protectiveness, reactivity, neuroticism, and fearfulness were the traits that emerged and that diversified themselves according to species. Moreover, intrinsic animal facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 60 publications
4
33
0
Order By: Relevance
“…Sociability showed a linear decline with age in months. Hence, it clearly demonstrates that Sociability/ dependency and playfulness were strongly affected by age, as in Menchetti et al [ 80 ]. This result complements the widespread view that older dogs play less in comparison to younger dogs.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Sociability showed a linear decline with age in months. Hence, it clearly demonstrates that Sociability/ dependency and playfulness were strongly affected by age, as in Menchetti et al [ 80 ]. This result complements the widespread view that older dogs play less in comparison to younger dogs.…”
Section: Discussionsupporting
confidence: 67%
“…Items loading on this factor were associated with playfulness and owner attachment/dependency. Sociability as reported by Menchetti et al [ 80 ] also included sociable and playfulness traits in dogs and cats. However, Sociability documented by Svartberg and Forkman [ 81 ] and Turcsán et al [ 35 ] included dogs’ social behaviour towards strangers such as greeting and approach behaviour, and cooperation and handling.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that familiarity with companion animals—in terms of ownership—was associated with a higher level of conferral of emotions to animals [ 42 ], which appeared to lead to a more pro-animal attitude [ 43 ]. Menchetti [ 44 ] also suggested that different attitudes to owned animals could be influenced by the perception of their personalities by owners.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the number of days of supplementation was included as covariate. Results were expressed as b coefficient with SE and p value from Wald Chi-square statistics [16,39].…”
Section: Statistical Considerations and Data Analysismentioning
confidence: 99%